Teacher cognition in teaching intercultural communicative competence: A qualitative study on preservice Chinese language teachers in Hong Kong SAR, China - Gong, Yang Frank; Lai, Chun; Gao, Xuesong (Andy); Li, Guofang; Huang, Yingxue; Lin, Lin (Frontiers in Psychology, 2022)
The purpose of this study is to examine preservice Chinese language teachers’ cognition in teaching intercultural communicative competence. In the study we collected data through in-depth interviews with seven preservice teachers in a Master of Education program (Teaching Chinese as a Second Language, TCSL) at a university in Hong Kong SAR. The findings indicated that the participants had a relatively positive attitude and inclination towards the development of students’ intercultural communicative competence, while their conceptualizations of culture tended to be static and ambiguous. In addition, the participants’ objectives in teaching intercultural communicative competence were found to be more attitude- than knowledge- or skill-oriented. The study offers valuable insights that preservice language teachers’ cognition plays a crucial role in their future professional development and calls for curricular innovations with intercultural aims in teacher education programs.